The use of a centrifuge-free RABiT-II system for high-throughput micronucleus analysis. (11th December 2019) - Repin, Mikhail; Pampou, Sergey; Brenner, David J; Garty, Guy
ABSTRACT: The cytokinesis-block micronucleus (CBMN) assay is considered to be the most suitable biodosimetry method for automation. Previously, we automated this assay on a commercial robotic biotech high-throughput system (RABiT-II) adopting both a traditional and an accelerated micronucleus protocol, using centrifugation steps for both lymphocyte harvesting and washing, after whole blood culturing. Here we describe further development of our accelerated CBMN assay protocol for use on high-throughput/high content screening (HTS/HCS) robotic systems without a centrifuge. This opens the way for implementation of the CBMN assay on a wider range of commercial automated HTS/HCS systems and thus increases the potential capacity for dose estimates following a mass-casualty radiological event.